Macroanatomic investigations on the lohation of the lungs and broncho-pulmonary segments in the angora rabbit - Bumin Emre Teke (Eurasian Journal of Veterinary Sciences)
Twelve adult male rabbits were used to investigate the lung lobalion and broncho-pulmoner segmentation. It was observed that there was no lobuli pulmonis on the facies externa of the both pulmones, pulmones formed 0.45% of the body weight and Ihe ralio of pulmo dexter to pulmo sinister was aproximately 3/5. It was found that pulmo dexter and sinister are consisted of four and two lobes respectively and lobus caudalis was the largest part of the both pulmones. A single lobe as big as a chickpea was seen on the facies diaphragmalica of the pulmo dexter in lour of the animals (33.3%). A sulcus was aproximately three mm dept which is lining trom dorsal to ventrocaudal was observed on the facies medialis ol the lobus caudalis of the pulmo sinister and a formation like a lamina on the lobus caudalis was seen due to this sulcus in five of the rabbits (41.6%). It was determined that bronchus principalis dexter and sinister consisted ol four and two bronchus respectively; the di«<mater of tlie trachea was five mm and the number of U shaped cartilago Irachealis was ranged from 45 to 50.